“Don't give me that look” - overconfidence in false mental state perception in schizophrenia - Köther, Ulf; Roesch-Ely, Daniela; Pfüller, Ute; Scheu, Florian (Psychiatry research, 2012)
Dysfunctions in social cognition are implicated in the pathogenesis of schizophrenia and have been extensively replicated over the years. For memory research, the administration of cognitive tasks with metacognitive aspects like confidence ratings has deepened our insight into how impairments contribute to symptoms of the disorder. A total of 76 patients with schizophrenia or schizoaffective disorder and a sample of 30 healthy participants were tested with the Reading the Mind in the Eyes test (Eyes-test). The Eyes-test was complemented with a rating scale requesting response confidence and was administered along with paradigms tapping neuropsychological parameters and cognitive insight. Schizophrenia patients showed impaired abilities on mental state perception. In addition, they committed more high-confidence errors and at the same time made fewer high-confidence correct responses. Impairments were most pronounced in patients with formal thought disorder. The patients displayed a decreased metacognitive awareness for their deficits. The results suggest that adding confidence ratings to the investigation of social cognition promises to advance our understanding of social cognition in schizophrenia. Patients not only show severe impairments in social cognition, but are overconfident in their judgments and lack cognitive insight into their deficits. The results highlight the need for metacognitive therapeutic approaches for the treatment of this population.
Gesehen am 14.11.2018